METHODOLOGICAL FOUNDATIONS FOR THE DEVELOPMENT OF INDEPENDENT COGNITIVE ACTIVITY THROUGH SELF-ASSESSMENT (on the example of Primary School students) - Mahmudova Nodira Alisherovna (Galaxy International Interdisciplinary Research Journal, 2023)
This article provides an idea of the methodological foundations of the development of independent cognitive activity through self-assessment, the possibilities of self-assessment, effective factors affecting the student’s self-assessment, as well as the main content of assessment in elementary school.